Axiomatizing bisimulation equivalences and metrics from probabilistic SOS rules - D'Argenio, Pedro Ruben (2014)
Fil: D'Argenio, Pedro Ruben. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.